FM fact label - Horcas-Aguilera, José Miguel; Galindo-Gómez, José; Fuentes-Fernández, Lidia; Benavides, David (Elsevier, 2024)
FM Fact Label is a tool for visualizing the characterizations of feature models based on their metadata, structural measures, and analytical metrics. Although there are various metrics available to characterize feature models, there is no standard method to visualize and identify unique properties of feature models. Unlike existing tools, FM Fact Label provides a standalone web-based platform for configurable and interactive visualization, enabling export to various formats. This contribution is significant because it supports the Universal Variability Language (UVL) and enhances the UVL ecosystem by offering a common representation of the results of existing analysis tools.
Keywords: Lenguajes de programación; Informática; Ingeniería del software; Characterization; Feature model; Metrics; Software product line; Variability; Visualization